Neutron induced light-ion production from Iron and Bismuth at 175 MeV - Bevilacqua R. (2015)
© 2010 Owned by the authors, published by EDP Sciences. We have measured light-ion (p, d, t, 3He and α) production in the interaction of 175 MeV neutrons with iron and bismuth, using the MEDLEY setup. A large set of measurements at 96 MeV has been recently completed and published, and now higher energy region is under investigation. MEDLEY is a conventional spectrometer system that allows low-energy thresholds and offers measurements over a wide angular range. The system consists of eight telescopes, each of them composed of two silicon surface barrier detectors, to perform particle identification, and a CsI(Tl) scintillator to fully measure the kinetic energy of the produced light-ions. The telescopes are placed at angles from 20° to 160°, in steps of 20°. Measurements have been performed at The Svedberg Laboratory, Uppsala (Sweden), where a quasi mono-energetic neutron beam is available and well characterized. Time of flight techniques are used to select light-ion events induced by neutrons in the main peak of the source neutron spectrum. We report preliminary double differential cross sections for production of protons, deuterons and tritons in comparison with model calculations using TALYS-1.0 code.